Book review: Crossing borders, writing texts, being evaluated: cultural and disciplinary norms in academic writing by Anne Golden, Lars Anders Kulbrandstad and Lawrence Zhang - Xiao, Yuehai (Mike); He, Jingyi; Sun, Li (Frontiers in Psychology, 2024)
co-edited a volume entitled "Crossing Borders, Writing Texts, Being Evaluated: Cultural and Disciplinary Norms in Academic Writing", aiming to inform teachers and researchers of academic writing of the challenges presented in multilingual contexts and propose solutions and coping strategies that are substantiated by empirical evidence. The book's premise is that academic writing is a border-crossing activity that requires understanding of cultural and disciplinary norms. The editors have gathered a collection of essays in the field to explore these norms and how they shape academic writing. The result is a rich tapestry of perspectives that can inform practitioners and researchers who are interested in the intersection of language, culture, disciplines and academic writing.The eight chapters are written by established scholars, who had cross border experiences themselves, residing in such countries as